Development of a Simple and Effective Water Disinfection System Using an Electrochemical Mixed Oxidants-Generating System to Remove Waterborne Pathogens in Developing Countries - 배경선; 김지예; 윤제용; 신귀암 (적정기술학회지(Journal of Appropriate Technology), 2023)
Despite tremendous efforts from various international agencies such as World Health Organization (WHO), waterborne diseases are a still major cause of morbidity and mortality in the world – with more than 1 billion incidences and more than 2 million deaths per year. As an effort to mitigate this global burden, we developed a water disinfection system using electrochemical mixed oxidants-generating system. This system is simple, inexpensive, and easy to use. In this study, we determined the effectiveness of the new water disinfection system against waterborne pathogens using Escherichia coli CN13, bacteriophage MS2 and Bacillus subtilis spores as bacterial, viral, and protozoa indicator organisms, respectively. The results of this study showed that the new water disinfection system is very effective against E. coli CN13 (~3 log10 inactivation within 3 minutes with 0.3 mg/L of free chlorine) and coliphage MS2 (> 4 log10 inactivation within 3 minutes with 0.5 mg/L of free chlorine) Although the inactivation of B. subtilis spores by the new disinfection system was some- what slow (~0.5 log10 inactivation in 60 minutes with 10 mg/L of free chlorine), the result is similar to previous studies with free chlorine. Overall, the results of this study indicate that the new water disinfection system using an electro- chemical mixed oxidants-generating system is easy to use, convenient to carry, and also very effective against most water- borne pathogens, so it could be a sustainable solution for providing safe drinking water to the people in developing countries.
Keywords: Waterborne diseases; Mixed oxidants; E. coli CN13; Bacteriophage MS2; Bacillus subtilis spores